Global variation in the fraction of leaf nitrogen allocated to photosynthesis - Xiangzhong Luo (Nature Portfolio, 2021)
The fraction of leaf nitrogen allocated to RuBisCO indicates differing nitrogen use strategies of plants and varies considerably. Here the authors show that this variation is largely driven by leaf thickness and phosphorus content with light intensity, atmospheric dryness and soil pH also having considerable influence.